A polycyclic aromatic hydrocarbon diradical with pH-responsive magnetic properties. Issue 21 (20th May 2020) - Fu, Xiangyu; Han, Han; Zhang, Di; Yu, Han; He, Qilin; Zhao, Dahui
Abstract : A novel polycyclic aromatic hydrocarbon molecule exhibiting manifold zwitterionic, diradical and quinoidal characteristics is designed and synthesized. Via reversible protonation, its pH-responsive magnetic properties are demonstrated. Abstract : By integrating azulene with a quinoid moiety, a novel non-alternant polycyclic aromatic hydrocarbon molecule BCHF1 exhibiting manifold zwitterionic, quinoidal and diradical behaviors is designed and synthesized. Its zwitterionic feature is evidenced by the changes shown by the 1 H-NMR and absorption spectra when the molecule undergoes reversible protonation and deprotonation reactions at varied pH. The diradical facet, manifesting a small singlet–triplet energy gap (Δ E S–T ), is characterized with a paramagnetic resonance signal detected by the EPR spectroscopy at room temperature. As the diradical properties are not observed in the protonated form, BCHF1+H +, a pH-controlled reversible magnetic switching behavior is illustrated by monitoring the on and off cycles of EPR signals upon successively adding bases and acids to a solution or exposing a thin film of BCHF1+H + to base vapor followed by acid vapor.